Effects of cerebellar transcranial magnetic stimulation on ataxias: A randomized trial. (November 2020) - França, Carina; de Andrade, Daniel C.; Silva, Valquíria; Galhardoni, Ricardo; Barbosa, Egberto R.; Teixeira, Manoel J.; Cury, Rubens G.
Abstract: Introduction: Cerebellar ataxia remains a neurological symptom orphan of treatment interventions, despite being prevalent and incapacitating. We aimed to study, in a double-blind design, whether cerebellar modulation could improve ataxia. Methods: We included patients with diagnosis of spinocerebellar ataxia type 3, multiple systems atrophy cerebellar type, or post-lesion ataxia. Patients received five sessions each of sham and active cerebellar 1 Hz deep repetitive transcranial magnetic stimulation in randomized order. Our primary outcome was the decrease in the Scale for the Assessment and Rating of Ataxia when comparing phases (active x sham). Secondary outcomes measures included the International Cooperative Ataxia Rating Scale, and other motor, cognitive, and quality of life scales. This study was registered at clinicaltrials.gov (protocol NCT03213106). Results: Twenty-four patients aged 29–74 years were included in our trial. After active stimulation, the Scale for the Assessment and Rating of Ataxia score was significantly lower than the score after sham stimulation [median (interquartile range) of 10.2 (6.2, 16.2) versus 12.8 (9.6, 17.8); p = 0.002]. The International Cooperative Ataxia Rating Scale score also improved after active stimulation versus sham [median (interquartile range) of 29.0 (21.0, 43.5) versus 32.8 (22.0, 47.0); p = 0.005]. Other secondary outcomes were not significantly modified by stimulation. No patient presented severe side effects, and nine presented mild and self-limited symptoms. Conclusions: Our protocol was safe and well-tolerated. These findings suggest that cerebellar modulation may improve ataxic symptom and provide reassurance about safety for clinical practice. Highlights: Cerebellar ataxia is an orphan symptom and currently lacks effective therapies. Cerebellar TMS showed a significant effect as a symptomatic therapy in ataxias. Symptomatic measures for ataxia included SARA and ICARS. Cerebellar TMS was safe in patients with cerebellar ataxias.